SUNNAH DALAM PERSPEKTIF ORIENTALIS - Kholik, Abdul (Institut Agama Islam Yasni Bungo, 2015)
The purpose of this article is to know movements and thoughts of Orientalist towards Sunnah of Prophet Muhammad (peace be upon him). Orientalisme is a term for movements in which its focus is to do research and study about language, social, religion, culture, civilization, etc, of the East (oriental). According to some writer, at least there are three purposes of orientalisme in Islamic world. First is for spreading of Christianity. Second is for colonialisme. Third is for sciences (knowledge) only. Beside that purpose, no doubt that orientalist?s studies also have many beneficial and contribution to knowledge in contemporary world. Sunnah as a second sourse of Islamic Law is not quiet from orientalist?s studies. Their studies (in some case) is to put Islam in doubt and always try in search of weakness of Sunnah. They talk and critic personal of hadits?s transmitter (rawi hadits) with dislike and tendentious in order to make sanction towards Sunnah Nabawiyyah. In this article, writer want to describe views of orientalist and some of Islamic thinkers towards hadits?s figures like Abu Hurairah and Imam Az-Zuhri, also give some critic to their thoughts. In reality, the effort for destroying of sunnah?s holy prophet Muhammad (Peace be upon him) starts from their figures. In spite of that, this article is not comprehensive cover of all their thought and movements.Keywords : Sunnah, Hadits, Orientalis dan orientalisme.